Evaluation of storage under pressure as a new preservation process to increase shelf-life of fresh fish - Fidalgo, Liliana Gonçalves (2020)
Hyperbaric storage at room and low temperature (HS/RT and HS/LT, respectively) was evaluated using Atlantic salmon (Salmo salar) as a case-study and compared to control samples stored at atmospheric pressure (AP) under refrigeration (AP/5 ºC) and at the same L T and RT temperatures. The work was developed based in two strategies: (1) a screening study was performed to define the best conditions of HS/RT and HS/LT, using salmon muscle portions; (2) and using the best conditions, it was studied the influence of HS on spoilage and inoculated surrogate-athogenic microorganisms in vacuum - packaged salmon loins, and important physicochemical parameters related to quality. According to the first study (1), HS/RT and HS/LT at 75 MPa/25 ºC and 60 MPa/10 ºC, respectively, caused a reduction of the initial microbial counts, increasing the microbial shelf-life of salmon muscle portions to at least 25 and 50 days, respectively, compared to AP/5 ºC (3 days). Additionally, both HS conditions did not cause changes in the physicochemical parameters studied, except an increase of lipid oxidation products, but less intensely compared to the respective control samples, AP/25 and 10 ºC. In general, activities of acid phosphatase, cathepsins B and D, and calpains decreased when compared to fresh salmon, with a more pronounced effect of storage temperature of 37 ºC (HS and AP samples). However, activity recovery was observed for some enzymes (cathepsins B and D, and calpains), with an activity increase at 60 MPa/10 ºC and 75 MPa/25 ºC after 50 and 25 days, respectively. Also, a pronounced increase of the myofibrillar fragmentation index (MFI) was observed at 75 MPa (25/37 ºC) after 10 days, with a decrease of sarcoplasmic proteins content also after 10 days with no further changes during the 25 days of storage. Otherwise, at 60 MPa/10 ºC, a decrease of MFI values was observed after 50 days of storage, with no effect for sarcoplasmic proteins during 30 days of storage, being verified only a slight increase after 50 days. In the second study (2), both conditions of 75 MPa/25 ºC and 60 MPa/10 ºC were evaluated for 30 days, using vacuum -packaged fresh salmon loins. HS allowed to decrease the initial population of spoilage and inoculated surrogate-pathogenic microorganisms, showing that besides the shelf-life extension, it also ensured better microbial safet y compared to control samples. Several physicochemical properties, such as drip loss, water holding capacity, textural properties, polyene index, fatty acids profile, lipid oxidation, MFI and volatile profile, were maintained to at least 15 days under both conditions. So, HS can represent an interesting food preservation methodology for extension of fresh salmon loins, with additional considerable energy savings for HS/RT when compared to refrigeration.